It takes a village to protect a child - Hendrick, Antonia; Young, S. (Social Workers Registration Board, 2013)
This article presents a case for taking a concerted community approach to protecting children. It does this through acknowledging that: child protection is indeed ‘everyone’s business’ (Landgren, 2005) and extending this into promoting a collective response rather than relying solely on child protection authorities to work with individual families; revisiting the ‘best interests’ criterion of child rights in protecting children; reiterating the argument (Young, McKenzie, Omre, Schjelderup, & Walker, 2014) for a much more nuanced understanding of, and response to, keeping children safe; and presenting some descriptions and analyses of community approaches to protecting children.